To solve this problem, let's simplify the expression step by step:
-6(1/4x - 2/3x + 5/6x)
First, simplify the parentheses by combining like terms inside:
-6(1/4x - 2/3x + 5/6x)
= -6(1/4 - 2/3 + 5/6)x
Next, find a common denominator for the fractions inside the parentheses, in this case, the least common multiple (LCM) of 4, 3, and 6, which is 12:
= -6(3/12 - 8/12 + 10/12)x
= -6(-5/12)x
Now, multiply the whole number -6 by the fraction (-5/12):
= (-6) * (-5/12) * x
= (30/12) * x
= 2 1/2 * x
Therefore, the simplified expression is 2 1/2x.
-6(1/4x - 2/3x + 5/6x)
Answers provided:
-2 1/2x
-x
2x
3/4x
1 answer